Muslim Nationalism from the Perspective of the Quran: Al-Mishbah’s Exegesis of Verses on the Fundamental Concepts of Nationalism - Marselina, Triya; Arnella, Ami Juwita (El-Rusyd, 2026)
This study is motivated by the ongoing debate regarding the relationship between Islam and nationalism, particularly the assumption that nationalism is a secular concept originating from the West and therefore incompatible with Islamic teachings. The study aims to analyze the concept of Muslim nationalism from the perspective of the Quran through the interpretation of relevant verses in Tafsir Al-Mishbah by M. Quraish Shihab. This research employs a qualitative library research approach using thematic (maudhu’i) Quranic interpretation. The primary data consist of the Qur’an and Tafsir Al-Mishbah, while secondary data are drawn from scholarly books, journal articles, and related literature. Data were collected through documentation and analyzed descriptively and interpretatively. The findings reveal that although the term "nationalism" is not explicitly mentioned in the Quran, its essential values are embedded in Islamic teachings, including unity, love for the homeland, justice, tolerance, obedience to legitimate authority, and respect for ethnic and cultural diversity. Quraish Shihab interprets these values as the foundation of a comprehensive concept of nationalism that promotes national solidarity without fostering hostility toward other nations. In conclusion, the Quran provides a strong moral and theological foundation for Muslim nationalism, demonstrating that patriotism and national commitment are compatible with Islamic principles and contribute to social harmony and national unity.